Playing Outdoors - Merete Lund Fasting (Scandinavian University Press (Universitetsforlaget), 2019)
This book explores the magic of spontaneous play self-organized by children. Outdoor play must be encouraged in kindergarten, in school and in community settings. Today, much of the time and play of children is organized by adults. This book is about the magic of self-organized play. Children express joy and independence in outdoor play. The author takes us along to play venues outdoors, showing us how cliffs, trees and groves are cherished sites of play. The book presents findings from two research projects on outdoor play, one from a kindergarten setting, one from school setting. In her research, Merete Lund Fasting has followed children in their play in the woods, along cliffs, in playgrounds and biking in their near surroundings, providing her with unique insights into the world of play.